Emergency and urgent dental visits among Medicaid enrollees from 2013 to 2017 - Rebekah Fiehn; Ilya Okunev; Mary Bayham; Steven Barefoot; Eric P. Tranby (BMC, 2020)
Abstract Background Better understanding of the frequency of dental emergencies and the procedures performed during those emergency visits can help providers, insurers, and policymakers understand workforce and care provision needs. Methods Procedures performed at an emergency dental encounter and in the encounter following that encounter are assessed. Emergency dental encounters are those with a CDT code of D0140, D0160, or D0170. Data was analyzed from the IBM Watson Medicaid Marketscan data from 2013 to 2017, a nationally representative dental and medical claims database from 13 deidentified states in the United States. Result Consistently over time, about 10% of all dental encounters are due to a dental emergency. 28% of emergency dental encounters had no other procedure performed during those encounters. When other procedures were performed during the encounter, the majority were diagnostic in nature, primarily radiographs. Among patients who returned to the dentists following an emergency visit, 43% returned for more definitive dental treatment, most within 30 days. Conclusions The majority of dental emergency encounters do not result in definitive treatment, rather patients often return to the dentist at a later date for that treatment. Where possible, dental providers could utilize teledental services to triage patients to appropriate care.